2002
DOI: 10.1128/jcm.40.6.2182-2186.2002
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence In Situ Hybridization with Peptide Nucleic Acid Probes for Rapid Identification of Candida albicans Directly from Blood Culture Bottles

Abstract: A new fluorescence in situ hybridization (FISH) method that uses peptide nucleic acid (PNA) probes for identification of Candida albicans directly from positive-blood-culture bottles in which yeast was observed by Gram staining (herein referred to as yeast-positive blood culture bottles) is described. The test (the C. albicans PNA FISH method) is based on a fluorescein-labeled PNA probe that targets C. albicans 26S rRNA. The PNA probe is added to smears made directly from the contents of the blood culture bott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
88
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(93 citation statements)
references
References 19 publications
3
88
0
Order By: Relevance
“…PNA probes have been used in several studies for the identification of Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Candida albicans in blood cultures. The sensitivities and specificities of these probes were all more than 98% (4,16,17,19,21). Although the sensitivity and specificity of individual probes (oligonucleotide and PNA) are very good, the usefulness of FISH as a diagnostic test depends on the probes included in the assay and is related to the prevalence of microorganisms in a specific setting.…”
mentioning
confidence: 99%
“…PNA probes have been used in several studies for the identification of Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Candida albicans in blood cultures. The sensitivities and specificities of these probes were all more than 98% (4,16,17,19,21). Although the sensitivity and specificity of individual probes (oligonucleotide and PNA) are very good, the usefulness of FISH as a diagnostic test depends on the probes included in the assay and is related to the prevalence of microorganisms in a specific setting.…”
mentioning
confidence: 99%
“…PCR-based methods and other successful molecular diagnostic techniques, such as the peptide nucleic acid-fluorescent in situ hybridization method (1,39,47), evaluating the hybridization of specific fluorescent probes to RNA target sites, have been developed, but their implementation for the identification of medically important yeasts in the clinical laboratory has not yet been routinely established, possibly because they are not so easy to perform and require more or less sophisticated equipment.…”
mentioning
confidence: 99%
“…[11,20,21] It has also been determined that PNA FISH test for C. albicans is more accurate than standard culture methods and results in significant cost saving. [31] Our results showed that FISH was compatible with PCR-RFLP and conventional methods, except multi-species candidemia.…”
Section: Discussionmentioning
confidence: 99%
“…in blood cultures are critical. [2,10,11] Current conventional methods for the identification of Candida spp. from positive blood cultures are based on subculture to appropriate fungal medium, including Sabouraud dextrose agar, or CHROMagar Candida medium, and isolated yeast colonies are identified by the phenotypic (germ tube formation, carbohydrate assimilation [e.g., API 20C, ID 32C], and chlamydospore formation on cornmeal agar).…”
mentioning
confidence: 99%
See 1 more Smart Citation